Evaluation of the Safety and Efficacy of a Novel Thrombin Containing Combination Hemostatic Powder Using a Historical Control. (24th May 2021) - Bruckner, Brian A.; Spotnitz, William D.; Suarez, Erik; Loebe, Matthias; Ngo, Uy; Gillen, Daniel L.; Manson, Roberto J.
This clinical study compares 2 hemostatic agents, a novel combination powder (CP) (HEMOBLAST ™ Bellows) and an established polysaccharide starch powder (PP) (Arista ™ AH) to assess the usefulness of CP. Retrospective comparative analysis of CP (July 2018 to July 2019, 68 patients) to PP (January 2011 to January 2013, 94 patients) in cardiothoracic patients was performed using linear regression models adjusting for age, sex, and procedure type for the endpoints: blood loss; protamine to skin closure time (hemostasis time); chest tube output and blood products required 48 hours postoperatively; ICU stay; postoperative comorbidities; and 30 day mortality. 162 patients (108 M: 54 F) underwent 162 cardiothoracic surgical procedures including: transplantation (n = 44), placement of ventricular assist device (n = 87), and others (n = 31). Use of CP compared to PP (Estimated Mean Difference [95% CI], P -value) produced significant reductions: blood loss (mL) (−886.51 [−1457.76, −312.26], P = 0.003); protamine to skin closure time (min) (−16.81 [−28.03, −5.59], P = 0.004); chest tube output (48 hrs, mL) (−445.76 [−669.38, −222.14], P < 0.001); packed red blood cell transfusions (units) (−0.98 [−1.56, −0.4], P = 0.001); and postoperative comorbidities (−0.31 [−0.55, −0.07], P = 0.012). There were no differences in the ICU stay (4.07 [−2.01, 10.15], P = 0.188) or 30-day mortality (0.57 [0.20, 1.63], P = 0.291). The use of CP in complex cardiothoracic operations resulted in improved hemostasis and significant clinical benefits in blood loss, transfusion requirements, morbidity, and time in operating room.